Analysis and Design Decision Support System of New English Teacher by Using Analytical Hierarchy Process (AHP) in EF English First Bali - Putri Suardani; I Made Adi Bhaskara; Komang Oka Saputra (International Journal of Engineering and Emerging Technology, 2017)
Abstract—The purpose of this study is to develop a decision support system to decide the best new English Teacher. The methods used are method of analysis, design method, and literature study. The learning method that is done is to survey the running company system, conduct interview with HRD, and analysis the survey. In literature study conducted by looking for references sources related to the research undertaken. The design is data management subsystem, knowledge base model and user interface. The results achieved are the creation of an application decision support system that can be used to select the most appropriate English teacher and in accordance with the criteria required. This system helps support the decision-making process for new English teacher. Keywords—system, decision, analytical hierarchy process (AHP)